Smart Investment Awareness: Introducing Safe and Productive Investment for Millennials - Wirasmi Wardhani; Muhammad Amin Kadafi; Ike Purnamasari; Arvita Rachmawaty; Irsan Tricahyadinata (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
The level of investment literacy among millennials is a crucial factor in personal financial management and long-term financial well-being. This study aims to analyze investment literacy levels, factors influencing investment interest, and the challenges faced by millennials in Balikpapan when investing. The research method employed is a survey with a quantitative approach targeting millennial respondents residing in Balikpapan. The findings indicate that most respondents have a basic understanding of investment, but it is still limited to common instruments such as time deposits and savings accounts. Their comprehension of portfolio diversification, risk management, and investment analysis remains low. The primary sources of information come from social media and seminars/webinars, while consultations with financial experts are rarely conducted. The factors influencing investment interest include perceived high risk, limited capital, and the influence of social environments and media. The main challenges faced are the lack of formal investment education and economic constraints. As a solution, this study recommends enhancing investment literacy through digital-based education, collaboration with financial institutions, and providing consultation or mentoring services.